Ketertelusuran Rantai Pasok Bahan Baku Farmasi Sebagai Upaya Peningkatan Kualifikasi dan Keamanan Pemasok - Alvita Labiibah Machsus; Holis Abdul Holik (STIKes Ibnu Sina Ajibarang, 2025)
The case of pediatric oral liquid formulations in Indonesia found to contain Ethylene Glycol (EG) and Diethylene Glycol (DEG) contaminants exceeding permissible limits was traced to propylene glycol excipients with inadequate supply chain traceability, resulting from pharmaceutical manufacturers' failure to implement proper supplier qualification in accordance with established standards. The aim of this study is to identify the stages in ensuring supply chain traceability and compare various national and international regulations related to supply chain traceability as part of supplier qualification. Based on the literature review conducted, it was found that there are still gaps between regulations in Indonesia and international regulations. Although regulations in Indonesia have made significant progress, there is still room for improvement and development in several areas such as risk management, evaluation systems, and documentation to enhance the safety and quality of pharmaceutical raw materials used in Indonesia.